Impairment of GABAergic system contributes to epileptogenesis in glutaric acidemia type I. (1st August 2017) - Vendramin Pasquetti, Mayara; Meier, Letícia; Loureiro, Samanta; Ganzella, Marcelo; Junges, Bernardo; Barbieri Caus, Letícia; Umpierrez Amaral, Alexandre; Koeller, David M.; Goodman, Stephen; Woontner, Michael; Gomes de Souza, Diogo Onofre; Wajner, Moacir; et al.
Summary: Objectives: Glutaric acidemia type I (GA‐I) is an inherited neurometabolic disorder caused by deficiency of glutaryl‐CoA dehydrogenase (GCDH) and characterized by increased levels of glutaric, 3‐OH‐glutaric, and glutaconic acids in the brain parenchyma. The increment of these organic acids inhibits glutamate decarboxylase (GAD) and consequently lowers the γ‐aminobutyric acid (GABA) synthesis. Untreated patients exhibit severe neurologic deficits during development, including epilepsy, especially following an acute encephalopathy outbreak. In this work, we evaluated the role of the GABAergic system on epileptogenesis in GA‐I using the Gcdh −/− mice exposed to a high lysine diet ( Gcdh −/− ‐ Lys). Methods: Spontaneous recurrent seizures (SRS), seizure susceptibility, and changes in brain oscillations were evaluated by video–electroencephalography (EEG). Cortical GABAergic synaptic transmission was evaluated using electrophysiologic and neurochemical approaches. Results: SRS were observed in 72% of Gcdh −/− ‐ Lys mice, whereas no seizures were detected in age‐matched controls ( Gcdh +/+ or Gcdh −/− receiving normal diet). The severity and number of PTZ‐induced seizures were higher in Gcdh −/− ‐ Lys mice. EEG spectral analysis showed a significant decrease in theta and gamma oscillations and predominant delta waves in Gcdh −/− ‐ Lys mice, associated with increased EEG left index. Analysis of cortical synaptosomes revealed a significantly increased percentage of glutamate release and decreased GABA release in Gcdh −/− ‐ Lys mice that were associated with a decrease in cortical GAD immunocontent and activity and confirmed by reduced frequency of inhibitory events in cortical pyramidal cells. Significance: Using an experimental model with a phenotype similar to that of GA‐I in humans—the Gcdh −/− mice under high lysine diet ( Gcdh −/− ‐ Lys)—we provide evidence that a reduction in cortical inhibition of Gcdh −/− ‐Lys mice, probably induced by GAD dysfunction, leads to hyperexcitability and increased slow oscillations associated with neurologic abnormalities in GA‐I. Our findings offer a new perspective on the pathophysiology of brain damage in GA‐I.